Metabolic Clinic Atlas: Organization of Care for Children with Inherited Metabolic Disease in Canada - Lamoureux, Monica F. (JIMD Rep, 2015)
Introduction: Nearly all children in Canada with an inherited metabolic disease (IMD) are treated at one of the country’s Hereditary Metabolic Disease Treatment Centres. We sought to understand the system of care for paediatric IMD patients in Canada in order to identify sources of variation and inform future research priorities. Methods: Treatment centres were contacted by email and invited to complete a web-based survey. The questionnaire addressed, for each centre, the population size served and scope of practice, available human resources and clinic services and research capacity. Survey responses were analyzed descriptively. Results: We received responses from 13 of the 14 treatment centres invited to participate. These centres represent at least 85% of the Canadian population, with over half of the centres located in southern Ontario and Quebec. All centres reported paediatric patients with IMDs as their main patient population. A variety of dedicated staff was identified; every centre reported having at least one physician and one dietician. The most common ancillary services available included telehealth (11/12 respondents) and biochemical genetic laboratory testing (10/12), with a high variability of access to on-site laboratory tests. A majority of centres indicated access to additional off-site services, but barriers to these were reported. All but one centre indicated previous experience with research. Conclusions: The variation we identified in the organization of care highlights the need to investigate the association between practice differences and health outcomes for paediatric IMD patients to inform policies that establish equitable access to services that are beneficial.